2022
DOI: 10.3390/molecules27020483
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Profile of Lipophilic Fractions of Different Parts of Zizyphus lotus L. by GC-MS and Evaluation of Their Antiproliferative and Antibacterial Activities

Abstract: Zizyphus lotus L. is a perennial shrub particularly used in Algerian folk medicine, but little is known concerning the lipophilic compounds in the most frequently used parts, namely, root bark, pulp, leaves and seeds, which are associated with health benefits. In this vein, the lipophilic fractions of these morphological parts of Z. lotus from Morocco were studied by gas chromatography–mass spectrometry (GC–MS), and their antiproliferative and antimicrobial activities were evaluated. GC–MS analysis allowed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 60 publications
0
8
0
1
Order By: Relevance
“…Additionally, fatty acid compounds identified and characterized as hydroxy-oleic acid (5), 23-methyl-5 Z ,9 Z -tetracosadienoic acid (11), trihydroxy-oleic acid (25), n -hexadecanoic acid (27), hexadecanoic acid, ethyl ester (28), docosanedioic acid (31), octadecanoic acid, ethyl ester (33) based on their m/z 298.036, 378.3493, 330.2762, 256.2388, 284.2933, 370.307, 312.5, respectively, and in accordance with the molecular formulas C 18 H 34 O 3 , C 25 H 46 O 2 ,C 18 H 34 O 5 , C 16 H 32 O 2 , C 18 H 36 O 2 ,C 22 H 42 O 4 , C 20 H 40 O 2 , respectively. A recent study conducted on the lipophilic fraction of different parts of Z. lotus revealed the identification of 99 compounds by GC/MS analysis, where the root bark showed the highest percentage of pentacyclic triterpenoids, especially betulinic acid, while the leaves and seeds were rich in unsaturated fatty acids [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, fatty acid compounds identified and characterized as hydroxy-oleic acid (5), 23-methyl-5 Z ,9 Z -tetracosadienoic acid (11), trihydroxy-oleic acid (25), n -hexadecanoic acid (27), hexadecanoic acid, ethyl ester (28), docosanedioic acid (31), octadecanoic acid, ethyl ester (33) based on their m/z 298.036, 378.3493, 330.2762, 256.2388, 284.2933, 370.307, 312.5, respectively, and in accordance with the molecular formulas C 18 H 34 O 3 , C 25 H 46 O 2 ,C 18 H 34 O 5 , C 16 H 32 O 2 , C 18 H 36 O 2 ,C 22 H 42 O 4 , C 20 H 40 O 2 , respectively. A recent study conducted on the lipophilic fraction of different parts of Z. lotus revealed the identification of 99 compounds by GC/MS analysis, where the root bark showed the highest percentage of pentacyclic triterpenoids, especially betulinic acid, while the leaves and seeds were rich in unsaturated fatty acids [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…This is the first comprehensive metabolites profiling of ZSC-L. using HPLC-ESI-MS. The metabolite profile of ZSC-L. indicates the presence of 11 flavonoids tentatively identified as quercetin 3,7,3 -trimethyl ether (4), eriodictyol-7-O-glucoside (7), apigenin-7-O-glucoside (8), okanin-4 -O-glucoside (15), quercitrin (17), isoquercetin (19), kaempferol-3-O-α-L-arabinoside (29), luteolin 7,3 -diglucoside (30), isoorientin 3 ,6 -di-O-glucoside (34), quercetin 3-O-robinobioside (35), rutin (36). Among these flavonoids, (17), (19), (34), (35) and (36) were previously isolated from ZSC-L [10,34] (12), ceanothic acid (13), zizyberanalic acid (14), betulinic acid (16), lupeol acetate (20), betulin (23), and zizyberenalic acid (26).…”
Section: Hplc-esi-ms/ms Analysis Of Different Extracts Of Zizyphus Sp...mentioning
confidence: 99%
See 1 more Smart Citation
“…Scientific studies have shown that the Z. mauritiana plant contains compounds that act as an antioxidant (Dahiru and Obidoa 2007;Bhatia and Mishra 2009;Gupta 2018), antimicrobial and antileishmanial (Abalaka et al 2010;Hammi et al 2022), and antidiabetic (Jarald et al 2009). The compound from the Z. mauritiana plant is also reported to have the ability to suppress the development of cancer cells (Zazouli et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The use of Z. mauritiana continues to grow as scientific evidence demonstrates diverse bioactive ingredients of the plants (Dahiru and Obidoa 2007;Bhatia and Mishra 2009;Jarald et al 2009;Delphine et al 2017;Askur and Ganning 2021;Hammi et al 2022;Zazouli et al 2022). Most of the analyses reported the utilization of wild or cultivated Z. mauritiana plants in a specific study area, but little is known about the secondary metabolites' profiles of the Z. mauritiana plant grown in a different environment.…”
Section: Introductionmentioning
confidence: 99%